Data-driven design and construction : 25 strategies for capturing, analyzing and applying building data - Deutsch, Randy (Hoboken : John Wiley & Sons Inc., 2015)
''In this comprehensive book, Professor Randy Deutsch has unlocked and laid bare the twenty-first century codice nascosto of architecture. It is data. Big data. Data as driver.This book offers us the chance to become informed and knowledgeable pursuers of data and the opportunities it offers to making architecture a wonderful, useful, and smart art form.' --From the Foreword by James Timberlake, FAIA Written for architects, engineers, contractors, owners, and educators, and based on today's technology and practices, Data-Driven Design and Construction: 25 Strategies for Capturing, Applying and Analyzing Building Data addresses how innovative individuals and firms are using data to remain competitive while advancing their practices. seeks to address and rectify a gap in our learning, by explaining to architects, engineers, contractors and owners--and students of these fields--how to acquire and use data to make more informed decisions. documents how data-driven design is the new frontier of the convergence between BIM and architectural computational analyses and associated tools. is a book of adaptable strategies you and your organization can apply today to make the most of the data you have at your fingertips. Data-Driven Design and Construction was written to help design practitioners and their project teams make better use of BIM, and leverage data throughout the building lifecycle'--
Includes index.
Keywords: Building -- Data processing; ARCHITECTURE / Professional Practice